2021
DOI: 10.1109/toh.2021.3052912
|View full text |Cite
|
Sign up to set email alerts
|

Visual Feedback Weakens the Augmentation of Perceived Stiffness by Artificial Skin Stretch

Abstract: Tactile stimulation devices are gaining popularity in haptic science and technologythey are lightweight, low-cost, can be easily made wearable, and do not suffer from instability during closed loop interactions with users. Applying tactile stimulation in the form of stretching the skin of the fingerpads, concurrently with kinesthetic force feedback, has been shown to augment the perceived stiffness during interactions with elastic objects. However, all of the studies to date have investigated the perceptual au… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…The standard virtual object always had a stiffness value of 85 N/m, and in trials with artificial skinstretch stimulation the skin-stretch gain was +80 mm/m in the positive stretch session, and -80 mm/m in the negative stretch session. This artificial skin-stretch gain was chosen because in our previous studies [27], [29] a clear augmentation in the perceived stiffness was demonstrated due to this level of positive artificial stretch. The stiffness level of the comparison virtual object was selected in each trial from a range of 12 values, evenly spaced between 30-140 N/m.…”
Section: Protocolmentioning
confidence: 99%
See 3 more Smart Citations
“…The standard virtual object always had a stiffness value of 85 N/m, and in trials with artificial skinstretch stimulation the skin-stretch gain was +80 mm/m in the positive stretch session, and -80 mm/m in the negative stretch session. This artificial skin-stretch gain was chosen because in our previous studies [27], [29] a clear augmentation in the perceived stiffness was demonstrated due to this level of positive artificial stretch. The stiffness level of the comparison virtual object was selected in each trial from a range of 12 values, evenly spaced between 30-140 N/m.…”
Section: Protocolmentioning
confidence: 99%
“…Recent studies showed that applying artificial skin-stretch in the same direction as kinesthetic load force augments the perceived stiffness linearly to the amount of stretch [27]- [29]. Additionally, this skin stretch increases the predictive grip force modulation in anticipation of the load force [27].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Ilana Nisky, 2021 Early Career Award winner, robot-assisted surgery can bridge the gap between laboratory-based research and real-life applications. Currently, surgical training is not optimized, partly due to a lack of haptic feedback and partly due to limited knowledge on how to measure surgical skills (4,11,23,30,45,45). Nisky's research used a teleoperated needle driving task and integrated data measuring the dynamics of the robotic manipulandum and modeling human kinematics to describe the quality of surgical skill throughout the learning process.…”
Section: Exploring Complex Motor Skills Beyond Unimanual Reachingmentioning
confidence: 99%